2018
DOI: 10.30773/pi.2017.07.24
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha-2A Adrenergic Receptor Gene -1291C/G Single Nucleotide Polymorphism is Associated with the Efficacy of Methylphenidate in Treating Taiwanese Children and Adolescents with Attention-Deficit Hyperactivity Disorder

Abstract: ObjectiveThe therapeutic effect of methylphenidate (MPH) in treating attention-deficit/hyperactivity disorder (ADHD) has been related to the alpha-2A adrenergic receptor (ADRA2A) gene -1291C/G single nucleotide polymorphism (SNP). We investigated the effect of MPH in treating Taiwanese children and adolescent with ADHD and its relation to the ADRA2A gene -1291C/G SNP. MethodsThe subjects with DSM-IV ADHD diagnosis underwent a titration period to find out the dose of MPH for maintenance treatment. After 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Although most research on the pharmacological effects of MPH in ADHD is focused on the dopaminergic system, there is a growing body of evidence pointing to the significance of the noradrenergic component as well. Not only has MPH a relatively high affinity for NAT, but it also directly interacts with noradrenergic receptors (Andrews and Lavin 2006 ; Besnard et al 2012 ; Furini et al 2017 ; Gamo et al 2010 ; Huang et al 2018 ). Accordingly, it was reported that MPH binds to several subtypes of α-adrenergic receptors: α 2A (K i = 5.6 µM), α 2B (K i = 2.420 µM), and α 2C (K i = 0.860 µM) (Wenthur 2016 ).…”
Section: Methylphenidate: Chemistry and General Pharmacologymentioning
confidence: 99%
“…Although most research on the pharmacological effects of MPH in ADHD is focused on the dopaminergic system, there is a growing body of evidence pointing to the significance of the noradrenergic component as well. Not only has MPH a relatively high affinity for NAT, but it also directly interacts with noradrenergic receptors (Andrews and Lavin 2006 ; Besnard et al 2012 ; Furini et al 2017 ; Gamo et al 2010 ; Huang et al 2018 ). Accordingly, it was reported that MPH binds to several subtypes of α-adrenergic receptors: α 2A (K i = 5.6 µM), α 2B (K i = 2.420 µM), and α 2C (K i = 0.860 µM) (Wenthur 2016 ).…”
Section: Methylphenidate: Chemistry and General Pharmacologymentioning
confidence: 99%
“…In the literature, the side effect of chorea associated with the use of methylphenidate in therapeutic doses or rapid dose increase for therapeutic purposes has been reported in children 5,6 . This condition is attributed to the prefrontal cortex alpha-2A adrenergic receptor gene polymorphism, which can increase the effectiveness of the drug, or the CES1 gene variation that delays the metabolism of the drug 7,8 . Our patient who had no history of consanguinity have a brother who was receiving 10 mg of methylphenidate daily due to ADHD and he had no side effects such as movement disorder etc..…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the ADRA2A-1291C/G SNP is associated with the efficacy of methylphenidate (MPH) in the treatment of attention deficit/hyperactivity disorder in children and adolescents in Taiwan. Reactive subjects carrying the homozygous-1291G allele are more likely to respond better to MPH therapy, indicating that the -1191C/G SNP is very sensitive to MPH (34). In addition, as seen from the results of the present study, the VAS score of wild-type puerperae was lower than the mutant puerperae at the same time after surgery, while the Ramsay scores of wild-type puerperae 12 h after surgery were significantly higher than the mutant puerperae, indicating that wild-type puerperae are more sensitive to dexmedetomidine than mutant puerperae, probably because genetic mutations alter the structure and/or function of the Figure 7.…”
Section: Discussionmentioning
confidence: 99%